Meaning in Music Is Intentional, but in Soundscape It Is Not - A Naturalistic Approach to the Qualia of Sounds - Welch, David; Reybrouck, Mark; Podlipniak, Piotr (MDPI, 2023)
The sound environment and music intersect in several ways and the same holds true for the soundscape and our internal response to listening to music. Music may be part of a sound environment or take on some aspects of environmental sound, and therefore some of the soundscape response may be experienced alongside the response to the music. At a deeper level, coping with music, spoken language, and the sound environment may all have influenced our evolution, and the cognitive-emotional structures and responses evoked by all three sources of acoustic information may be, to some extent, the same. This paper distinguishes and defines the extent of our understanding about the interplay of external sound and our internal response to it in both musical and real-world environments. It takes a naturalistic approach to music/sound and music-listening/soundscapes to describe in objective terms some mechanisms of sense-making and interactions with the sounds. It starts from a definition of sound as vibrational and transferable energy that impinges on our body and our senses, with a dynamic tension between lower-level coping mechanisms and higher-level affective and cognitive functioning. In this way, we establish both commonalities and differences between musical responses and soundscapes. Future research will allow this understanding to grow and be refined further.
Keywords: music; soundscape; sound environment; soundscape descriptors; musical affordances; coping behavior